Architectural Coloured Illumination Application for Wayfinding in Exhibition Centre - Chua, Kim Han; Syed Fadzil, Sharifah Fairuz (MAJ - Malaysia Architectural Journal, 2020)
Colour is one of the powerful wayfinding elements that helps the users to navigate inside the building space. This research will explore and identify the wayfinding performance using architectural coloured illumination in the exhibition centre, in terms of user’s perception and preference of colours and illumination method using architectural elements. The reason for this subject matter is due to the issue of less effective wayfinding performance from conventional way finding method such as signage, landmarks or even spaces themselves. Thus, coloured illumination as universal wayfinding method has potential to maximise the wayfinding capability. Mixed method data collection is used in this research, consists of qualitative and quantitative method. Case studies regarding the certain buildings in Malaysia that uses artificial coloured illumination is used as qualitative method. The data obtained from the qualitative method is used to structure the quantitative method, which is the questionnaire survey. An online survey conducted in the form of questionnaire for designer target group with different age groups regarding the research and the subject matters. From the survey, respondents are given with choices of preferred colour of basic colours. They are also given with choices of preferred architectural coloured illumination technique of illumination using wall, floor and ceiling. As the result, the overall preferred architectural coloured illumination is yellow coloured hue with illumination on the wall. The findings from this research can be used as an information for designers and architects to further maximise the wayfinding performance to create more effective wayfinding in buildings.